Mannen med pappnesen (Polarboken, 1986)
Keywords: Antarktis; ekspedisjoner; fotografi; historie

Det internasjonale samarbeid i Antarktis og forhandlingene om et mineralregime - Andersen, Rolf Trolle (Polarboken, 1986)
Keywords: Antarktis; mineraler; politikk

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Oppfinere og teknologisk utvikling i norsk hvalfangsthistorie - Basberg, Bjørn L (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; Norge; harpuner; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Da hvalfangerne organiserte seg. Forholdet mellom sosial mobilitet og organisering - Devig, Thor N (Sandefjordmuseene. Årbok, 1986)
Keywords: Sørishavet; arbeidsforhold; fagforbund; fagforeninger; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri

Botany of two Antarctic mountain ranges: Gjelsvikfjella and Mühlig-Hofmannfjella, Dronning Maud Land. I. General ecology and development of the Antarctic cold desert cryptogam formation - Engelskjøn, Torstein (Polar Research, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; forskning; planter

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

Kaptein C.A. Larsen: mannen som grunnla den moderne hvalfangsten i Sydishavet - Fagerli, Torkel (Polarboken, 1986)
Keywords: Sørishavet; biografi; historie; hvalfangst

Genetic variation of Euphausia superba Dana in the Antarctic Peninsula waters - Fevolden, Svein Erik (Sarsia, 1986)
Nine samples of Antarctic krill collected at seven localities in the Palmer Archipelago and Bransfield Strait west of the Antarctic Peninsula were analysed for genetic variation at eight enzyme loci. Despite significant among sample heterogeneity in allele frequencies, no convincing evidence was found to support the hypothesis of distinct genetic stocks of Euphausia superba in the investigated area. Allele frequency distributions could not be correlated to regional differences in size patterns. Allelic proportions at the PGI locus did not indicate that the investigated krill was genetically different from E. superba from the Weddell Sea region (from earlier investigations). Deviations of genotypes, or allele frequencies from those expected under Hardy-Weinberg equilibrium, however, may indicate regional, or yearly variation due to occasional selection.
Keywords: Sørishavet; Weddellhavet; genetikk; krill; plankton

Oceanographic research during NARE-84/85 - Foldvik, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1986)
Keywords: Sørishavet; oseanografi

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

A quantitative analysis of the behaviour of the Chinstrap penguin Pygoscelis antarctica and Macaroni penguin Eudyptes chrysolophus on Bouvetoya during the late incubation and early nestling periods - Haftorn, Svein (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; pingviner; zoologi

Antarktis petrellen - verdens mest hardføre fugl? - Haftorn, Svein (Viten : populær vitenskap, 1986)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Hvalfangernes gravsteder i Antarktis - Headland, Robert K (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; historie; hvalfangere; hvalfangstindustri; hvalfangststasjoner; hvalindustri

Monica på veg til 90° syd - Heimark, Kjell Gunnar (Været: populærvitenskapelig tidsskrift, 1986)
Keywords: Antarktis; ekspedisjoner

Proteases of Antarctic krill—a new system for effective enzymatic debridement of necrotic ulcerations - Hellgren, L.; Mohr, Viggo; Vincent, J. (Experientia, 1986)
The Antarctic krill (Euphausia superba) possesses an ‘over-dimensioned’ digestive system, which is of vital importance for the survival of this euphaucean shrimp in the extreme marine environment. The isolated enzymes contain a well-balanced mixture of both endo- and exopeptidases, assuring fast and complete breakdown of proteinaceous material. These unique properties have now been shown to be extremely valuable for the effective removal of necrotic debris, fibrin or blood crusts in vitro. Therefore the krill enzymes should be considered as an important resource in the future management of necrotic wounds.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Utviklingen i internasjonal forvaltning av hval 1975-1985: politisk mobilisering, økonomisk marginalisering - Hoel, Alf Håkon (Fridtjof Nansens institutt, 1986)
Keywords: Sørishavet; forvaltning; hvalfangst

Antarctic ozone depletion: 2-D model studies - Isaksen, Ivar S. A.; Stordal, Frode (Geophysical Research Letters, 1986)
Antarctic ozone depletion is estimated in a 2-D global model as a result of increase in chlorine levels from 1 ppb to 2.7 ppb and an increase in bromine levels from 15 ppt to 30 ppt. The adopted increase is assumed to be the anthropogenic influence on the stratospheric concentrations of chlorine and bromine species in 1985. Heterogeneous formation of ClO from the reaction between ClONO2 and HCl is included in the calculations, hypothesizing this is the dominant reaction path for chlorinated species on particle surfaces. A total ozone depletion as high as 14-20% may have occurred during the month of October at 80°S when maximum depletion is obtained. Both the magnitude and the time period when the maximum depletion occurs, agree with observed depletion over the last 8 years.
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Macrolichens of Bouvetøya - Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

The supralittoral, freshwater and terrestrial algal vegetation of Bouvetøya - Klaveness, Dag; Rueness, Jan (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; alger; botanikk

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Norge i Antarktis - Luraas, Ragnar; Kjærvik, Atle (Norsk journalisthøgskole, 1986)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; politikk

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Petreller i Dronning Maud Land - Mehlum, Fridtjof (Polarboken, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Glaciological research on the Norwegian Antarctic Research Expedition (NARE) 1984/85 - Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1986)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis

Flow and thickness of Riiser-Larsenisen, Antarctica - Orheim, Olav; Drewry, David (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Crustose lichens of Bouvetøya - Øvstedal, Dag Olav (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lichens and lichen parasites from the British-Swedish-Norwegian antarctic expedition 1949-52 to Dronning Maud Land - Øvstedal, Dag Olav (Cryptogamie: bryologie, lichenologie, 1986)
Keywords: Dronning Maud Land; botanikk; ekspedisjoner; lav; parasitter; planter

Lichencolous ascomycetes from Bouvetøya - Øvstedal, Dag Olav; Hawksworth, David L (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Photoadaptation in Antarctic phytopfankton: variations in growth rate, chemical composition and P versus I curves - Sakshaug, Egil; Holm-Hansen, Osmund (Journal of Plankton Research, 1986)
The response of phytoplankton to variations in the light regime was studied during the VULCAN and ACDA cruises in the Antarctic. Unenriched batch cultures of 12–19 days' duration reached chl concentrations of 10–50 μg−1 and exhibited exponential growth rates, with the maximal rate being 0.41 doubl, day−1. Ice edge algae exhibited maximum growth rates at photon flux densities (PFD) of 30–100 μE m−2S−1 and the growth rate was reduced by about 30% at 500–1000 μE m−2S−1 The chl/C ratio ranged between 0.004 and 0.018, with the lowest ratios at PFDs above 500 μE m−2S−1 chl/C ratios were also below maximum at PFDs below 40–50 μE m−2S−1 The C:N:P ratios were close to the Redfield ratios; the Si/C ratio averaged 0.16 (atoms), and the ATP/C ratio averaged from 0.0024 to 0.0050 in different culture senes. When thawed after having been frozen for 10 days, shade-adapted cultures were in a much better condition than sun-adapted ones. P versus I data showed that the maximum assimilation number varied from 0.75 to 4.4 μg C (μg chl)−1h−1. It varied inversely with the chl/C ratio; therefore the maximum carbon turnover rate varied little between samples (0.024/0.035 h−1). Low biomass communities exhibited relatively high values for α (the initial slope of P versus I curves), low values for 1sat (160–330 μE m−2S−1), and they were susceptible to photoinhibition. In contrast, communities dominated by Odontella weissflogii exhibited low values for α, a high value for Isat (560 μE m−2S−1 and they tolerated high PFDs. The photo-adaptational status of the phytoplankton in natural water samples is discussed relative to the profile of water column stability and mixing processes.
Keywords: Sørishavet; alger; biokjemi; fytoplankton; marin biologi; oseanografi; planteplankton

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Noen norske stedsnavn på Syd Georgia - Thoresen, Per (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; historie; hvalfangere; hvalfangstindustri; hvalfangststasjoner; hvalindustri